Lajpat Rai and Human Rights: Exploring Lala Lajpat Rai's Contribution to Human Rights Movement in India (Journal of Advances and Scholarly Researches in Allied Education, 2013)
The concept of human rights has been the centre to the concept of Indian thought. A large number of religious preachers, activists and visionaries have been the torch bearers for exploring the cause of the human rights. One may, recall the teachings of Budha, Mahavira, Kabir, Guru Nanak Dev, Sant Namdev, Sri Ramakrishan and many others. In the 20th Century Dayanand Saraswati, Vivekanand, Raja Ram Mohan Roy, Ishwar Chander Vidyasagar, Mahatma Gandhi, B.R. Ambedkar, Lala Lajpat Rai created a movement for equality and end to social discrimination. They made intensive efforts to ensure various human rights to weaker and marginal sections of the society. They stoutly raised their voices against violation of human rights and worked to eradicate it through personal examples and missionary zeal contribution of one of these propagandists, Lala Lajpat Rai needs attention.Most of us recognise Lala Lajpat Rai as a patriot, freedom fighter and one of the trio Lal-Bal-Pal. He was also known for his fearlessness and challenging spirit - the one who fought against the British empire and laid down his life as a martyr. His crusade for the rights of weaker sections of society espically the women, depressed classes labour and victims of natural calamities provide another aspect of his dynamic, multifacial personality.